(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract The aim of the research is to identify the level of awareness and emotional experience among university students and to identify the effect of the educational program based on (Guttmann) model for developing awareness and emotional experience among university students by verifying the validity of the following zero hypotheses: 1) There are no statistically significant differences in the development of awareness and emotional experience among university students at the level of (0.05) between the mean scores of the experimental group in the pre and post-tests. 2) There are no statistically significant differences in the development of awareness and emotional experience among university students at the level of (0.05) between the mean scores of the control group in the pre and post-tests. 3) There are no statistically significant differences in the development of awareness and emotional experience among university students at the level of (0.05) between the mean scores of the experimental group and the mean scores of the control group in the post-test. The researchers developed an instrument for measuring awareness skills and emotional experience through a question posed about how to respond to emotional situations and the individual’s ability to emotionally control through and after the emotional situation. The two researchers developed an educational program based on the Guttmann model, which consisted of (16) lessons that continue for (50) minutes of each lesson. The experimental group consisted of (40) students: (20) males, and (20) females selected intentionally from the first class at the College of Basic Education. A pre-test was conducted to find out awareness skills and emotional experience. The experimental pre-posttest design with a single group was chosen as it fits the research sample. The findings of the research revealed there is a statistically significant difference in the level of awareness skills and emotional experience after exposure to the program. There are no statistically significant differences in the development of awareness skills and emotional experience among university students, as well as between the mean scores of the control group in the pre and post-tests. There are statistically significant differences between the mean scores of the experimental group and the control group in the post-test in developing awareness skills and emotional experience in favor of the experimental group. The researchers presented a set of recommendations and suggestions.